Multidrug-resistant Enterobacterales infections in abdominal solid organ transplantation. (January 2023) - Pilmis, Benoît; Weiss, Emmanuel; Scemla, Anne; Le Monnier, Alban; Grossi, Paolo Antonio; Slavin, Monica A.; Van Delden, Christian; Lortholary, Olivier; Paugam-Burtz, Catherine; Zahar, Jean-Ralph
Abstract: Background: Transplant recipients are highly susceptible to multidrug-resistant (MDR) related infections. The lack of early appropriate antimicrobial treatment may contribute to the high mortality due to MDR-related infections in transplant recipients especially in case of metallo-β-lactamases. Objectives: In this review, we present the current state of knowledge concerning multidrug-resistant Gram negative bacilli's risk management in the care of solid-organ transplant recipients and suggest control strategies. Sources: We searched for studies treating MDR g-negative bacilli related infections in the renal and hepatic transplant patient population. We included randomized and observational studies. Content: Solid-organ transplant is the best therapeutic option for patients diagnosed with end-stage organ disease. While the incidence of opportunistic infections is decreasing due to better prevention, the burden of "classical" infections related to MDR bacteria especially related to Gram-negative bacteria is constantly increasing. Over the last two decades, various MDR pathogens have emerged as a relevant cause of infection in this specific population associated with significant mortality. Several factors related to the management of transplant donor candidates and recipients increase the risk of MDR infections in transplant recipients. The awareness of this high susceptibility of transplant recipients to MDR-related infections challenges the choice of empirical therapy, while its appropriateness can only be validated a posteriori. Indeed, the lack of early appropriate antimicrobial treatment may contribute to the high mortality due to MDR-related infections in transplant recipients especially in case of metallo-β-lactamases. Implications: Multidrug-resistant Gram-negative bacteria are associated with high morbidity and mortality in solid organ transplant recipients. It seems important to identify patients at risk of colonization/MDR bacteria to evaluate strategies to limit the risk of secondary infections and to minimize the inappropriate use of broad-spectrum antibiotics.